The Influence of Breed and Type of Extender on the Quality of Bull Semen - Sukirman, Iman; Sukmawati, Eros; Rasad, Siti Darojah; Solihati, Nurcholidah (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
This study aimed to determine the influence of breed and type of extenders on frozen semen quality of cows at BIB Lembang. The experimental study was conducted in a Factorial Randomized Block Design (RBD) with two factors. The first factor was four cow breeds, i.e. Ongole Cross (PO), Brahman (BR), Simmental (SM) and Limousin (LM), and the second factor was two types of extender, i.e. Skim-Egg Yolk (SKT) and AndroMedÂ® (AND), all repeated four times. The observed variables were percentage of spermatozoa motility and intact plasma membrane (IPM). All data obtained were analyzed using a general linear model (IBM SPSS ver. 23). The results demonstrated an interaction between breed and the type of diluent to motility. Breeds showed significantly different motility but non-significantly different intact plasma membrane (MPU) of semen. The type of diluent did not significantly affect motility and intact plasma membrane (MPU) of the frozen semen. The effect of the breed on BR motility was lower and significantly different from PO, LM and SM. The types of diluent did not significantly affect motility, MPU. The results showed that SKT was lower than AND, it was indicative effect of breed on intact plasma membrane (MPU) PO was lower than BR, LM and SM and the effect of the type of diluent on whole plasma membrane (MPU) AND is lower than SKT. It can be concluded that breed influences the motility of semen. The lowest motility reduction in frozen semen is Brahman cattle by using skim-egg yolk extender.